ESL writing self-efficacy: contribution to ESL writing skills development - Jalaluddin, Ilyana; Yamat, Hamidah; Md Yunus, Melor (International Organization Of Scientific Research, 2013)
This case study aims to understand how writing self-efficacy level contributes to the development of learners’ writing skills. The participants of this study consist of three form four learners and their English teacher. Here, teacher’s assistance would act as the mechanism to develop the learners’ writing self-efficacy. In order to gather information on teacher’s assistance, learners’ writing skills and writing self-efficacy, various types of data were collected: observation, questionnaire and interview. Though this research on self-efficacy and writing is not a new area in educational research, the findings still can be the added to the existing body of knowledge. Based on the finding derived from this study, two theoretical implications are discussed in this paper. The first part of theoretical implication centred on the reciprocal relationship of cognitive and behavioural engagement. Then the second part discussed the inclusion of teacher’s assistance component to the self-efficacy framework. Both of these implications had become the additional components to the existing framework which was proposed by Linnenbrink and Pintrich (2003).